Dual-responsive polypeptide nanoparticles attenuate tumor-associated stromal desmoplasia and anticancer through programmable dissociation. (May 2022) - Hsieh, Pei-Hsuan; Huang, Wei-Yuan; Wang, Huan-Chih; Kuan, Chen-Hsiang; Shiue, Ting-Yun; Chen, Yunching; Wang, Tzu-Wei
Graphical abstract: Image 1